The application of technology portable fertigation system in the dry month in tea plantation - Rahardjo, Pudjo; Wulansari, Restu; Pranoto, Eko (Research Institute for Tea and Cinchona, 2015)
The research aims at providing multifunction both irrigation and fertilizer applications (fertigation) and calculates the production of shoots and evaluated plant health during dry season. This research was carried out on Gambung Research Station using clone GMB7. Randomized block design was used in this study with six treatments and four replications. The treatments i.e. a. control (without irrigation, without fertilization); b. without irrigation, fertilization through the soil; c. irrigation 7 mm/day every 3 days (without fertilization); d. irrigation 7 mm/day every 6 days (without fertilization); e. fertigation 7 mm/day every 3 days; and f. fertigation 7 mm/day every 6 days. Observations were made from September-October 2014 with 4 times of plucking. All treatments were significantly different on the yield, number of both pecco and banji. The fertigation treatment using 21 mm of water (7 mm/day every 3 days) showed the highest shoot production of 15,56%. The highest number of pecco shoots and ratio of the number pecco/number of banji in treatment using 21 mm of water (7 mm/day every 3 days) of 32,25%. The highest number of banji found in the control treatment (without irrigation without fertilization) was 74,94%. From this research it can be concluded that the fertigation treatment can give good impact to production maintain and plant health in the dry season.